Generalized Euler equations in quaternions - Koshlyakov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The quaternion analog of the Euler dynamic equations obtained in [1–3] is generalized to the case of an arbitrary trihedron connected with a body.